2023
DOI: 10.3390/ijms24032003
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrophobic Effect Studied by Using Interacting Colloidal Suspensions

Abstract: Interactions between nanoparticles (NPs) determine their self-organization and dynamic processes. In these systems, a quantitative description of the interparticle forces is complicated by the presence of the hydrophobic effect (HE), treatable only qualitatively, and due to the competition between the hydrophobic and hydrophilic forces. Recently, instead, a sort of crossover of HE from hydrophilic to hydrophobic has been experimentally observed on a local scale, by increasing the temperature, in pure confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…80 It has been proposed earlier that the minimized susceptibility to pressure change revealed in these anomalies indicates the establishment of the most compact supra-molecular arrangement rather at the temperature of T * ≈ 315 K than at the actual density maximum. 67,77,78,81 As simulation studies suggested before, 82 our findings now confirm experimentally that, despite the different temperatures at which they occur, the density maximum and the mentioned pressure-related anomalies are caused by the same anomaly in the supra-molecular arrangement.…”
Section: B Thermal Expansionsupporting
confidence: 87%
See 3 more Smart Citations
“…80 It has been proposed earlier that the minimized susceptibility to pressure change revealed in these anomalies indicates the establishment of the most compact supra-molecular arrangement rather at the temperature of T * ≈ 315 K than at the actual density maximum. 67,77,78,81 As simulation studies suggested before, 82 our findings now confirm experimentally that, despite the different temperatures at which they occur, the density maximum and the mentioned pressure-related anomalies are caused by the same anomaly in the supra-molecular arrangement.…”
Section: B Thermal Expansionsupporting
confidence: 87%
“…This assignment is corroborated by the coincidence with the temperature of several anomalies related to the susceptibility of the material to pressure; past studies have suggested a single characteristic temperature T * ≈ 315 K for all these anomalies. 67,77,78,81 Here, we would like to note that for the determination of T * through these anomalies, exhaustive measurements in the temperature and pressure parameter spaces have to be carried out. In contrast, with the presented method, it is possible to identify T * without varying the pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations